2022
DOI: 10.3390/epigenomes6010008
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Networking: Plant Polycomb Repressive Complex 2 and Its Interactors

Abstract: Polycomb Repressive Complex 2 (PRC2) is arguably the best-known plant complex of the Polycomb Group (PcG) pathway, formed by a group of proteins that epigenetically represses gene expression. PRC2-mediated deposition of H3K27me3 has amply been studied in Arabidopsis and, more recently, data from other plant model species has also been published, allowing for an increasing knowledge of PRC2 activities and target genes. How PRC2 molecular functions are regulated and how PRC2 is recruited to discrete chromatin re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 175 publications
0
25
0
Order By: Relevance
“…Moreover, the marks brought at targets by PRC2 and trxG Histone Methyl Transferases (HMTs) are mutually exclusive, through direct prevention of each other’s enzymatic activity (Schmitges et al ., 2011)(Finogenova et al ., 2020). PRC2 and trxG activities have counterparts in plants, the PRC2 complex being the best conserved (Engelhorn et al ., 2014)(Bieluszewski et al ., 2021)(Baile et al ., 2022); however, differently from animals, most PRC2 mutants are viable in plants, likely due to redundancies of factors and multiplicity of complexes (Mozgova & Hennig, 2015)(Shu et al ., 2020)(Bieluszewski et al ., 2021)(Godwin & Farrona, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the marks brought at targets by PRC2 and trxG Histone Methyl Transferases (HMTs) are mutually exclusive, through direct prevention of each other’s enzymatic activity (Schmitges et al ., 2011)(Finogenova et al ., 2020). PRC2 and trxG activities have counterparts in plants, the PRC2 complex being the best conserved (Engelhorn et al ., 2014)(Bieluszewski et al ., 2021)(Baile et al ., 2022); however, differently from animals, most PRC2 mutants are viable in plants, likely due to redundancies of factors and multiplicity of complexes (Mozgova & Hennig, 2015)(Shu et al ., 2020)(Bieluszewski et al ., 2021)(Godwin & Farrona, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The only proteins that have been related to H2A deubiquitination in Arabidopsis are the closely related UBP12 and 13 proteins, which were identified interacting with LHP1 26 , a protein that may act as an accessory protein in both PRC2 and PRC1 7 . UBP12 was shown to be involved in the repression of a subset of PRC2 targets mediating H3K27me3 deposition and to be actively involved in H2A deubiquitination 26 .…”
Section: Discussionmentioning
confidence: 99%
“…PRC2 is a four-core subunit complex in which the catalytic component is a SET (Su(var), Enhancer of zeste, Trithorax) domain histone methyltransferase (HMT) 5, 6 . Analyses in different plant genomes showed that PRC2 decorates approximately 20-25% of euchromatic genes with H3K27me3, which switches them off in response to internal and external cues 7, 8 . In plants, PRC1 is formed by E3 ligases and other auxiliary proteins 5, 9 .…”
Section: Introductionmentioning
confidence: 99%
“…PcG genes were discovered in Drosophila ( Drosophila melanogaster ), and homologs of PcG components and their target genes have been identified in other eukaryotes including plants [ 173 , 174 , 175 , 176 ]. The role of the PRC2-mediated deposition of H3K27me3 has been studied in the context of developmental processes and environmental stress responses in plant model species including Arabidopsis [ 172 , 177 , 178 , 179 ]. The PRC1-like protein LHP1 (like heterochromatin protein-1) was also identified in Arabidopsis [ 166 , 180 , 181 ].…”
Section: Transcriptional Memory Of Drought Tolerancementioning
confidence: 99%